The values included in the general repository of second generation Arabic language curricula and textbooks for the primary cycle - Boulkamh, Mohamed; Sellama, Hanane Kaouther (Journal of Human Sciences, 2022)
The objective of this study is to reveal the degree of presence of values ​​in the general referential framework of methods, textbooks of the Arabic language in the first year, the second, the third, the fourth and the fifth year of the primary cycle. To achieve these objectives, the two researchers employed the descriptive analytical method by analyzing the content of Arabic language textbooks. The tool of our study was built from educational literature and previous studies related to our theme and its validity and reliability were confirmed. In light of this, the content of the general reference for the curricula and the content of Arabic language books for the primary stage were analyzed. The results of the study revealed an arrangement of the areas of values as follows: The area of moral and social values (46.81%). The field of health and aesthetic values (24.67%), the field of devotional values (7.12%), and finally the field of ideological values (1.76%).